1993
DOI: 10.1017/s0889189300005385
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration as a tool for detecting soil changes due to cropping, tillage, and grazing livestock

Abstract: Soil physical and biological properties often change when different cropping, tillage, or management systems are imposed. Changes occasionally occur quickly, but usually become evident only after months or years. Infiltration rates are affected by several soil properties and may provide the most sensitive indication of changes in soil properties. To evaluate the use of infiltration measurements for detecting changes in soil properties, we conducted infiltration tests on a cropping systems experiment, a tillage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 19 publications
(24 reference statements)
2
38
1
1
Order By: Relevance
“…Increased infiltration rate associated with well-structured soil decreases surface runoff and in turn reduces soil erosion. Radke and Berry (1993) observed that increases in soil bulk density due to soil use and management, e.g., tillage operation as well as raindrop impact, reduced infiltration rate in their study. Gumbs and Warkent in (1972) showed that a large decrease in infiltration rate resulted from a small increase in bulk density.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Increased infiltration rate associated with well-structured soil decreases surface runoff and in turn reduces soil erosion. Radke and Berry (1993) observed that increases in soil bulk density due to soil use and management, e.g., tillage operation as well as raindrop impact, reduced infiltration rate in their study. Gumbs and Warkent in (1972) showed that a large decrease in infiltration rate resulted from a small increase in bulk density.…”
Section: Introductionmentioning
confidence: 81%
“…In addition, soil texture directly affects soil moisture redistribution through its effect on soil permeability and on the hydraulic conductivity, which expresses how easily water flows through the soil, as well as the water holding capacity, and ultimately the infiltration rate. Soil structure and its surrogate, soil aggregates, influences infiltration characteristics and have been used as a good indicator of changes in soil physical and biological properties (Radke and Berry, 1993). Well structured soils have optimum infiltration rates at varying moisture levels.…”
Section: Introductionmentioning
confidence: 99%
“…Water infiltration is affected by various factors such as soil texture and structure, landscape position, management system, soil organic carbon, vegetative cover, antecedent water content, and rainfall intensity (Radke and Berry 1993). Vegetative covers have been found to increase soil organic carbon which improves soil properties and increases water infiltration rates.…”
Section: Introductionmentioning
confidence: 99%
“…In these buffer systems where the tree and grass buffer areas are left undisturbed by grazing animals, soil properties are different compared to pasture areas (Kumar et al 2008(Kumar et al , 2010a. Uneven grazing in continuously stocked pastures has been shown to lower water infiltration rates because of soil compaction in certain areas (Daniel et al 2002;Radke and Berry 1993;Wheeler et al 2002). However rotationally stocked pastures, where rest periods are provided to allow forage to recover between grazing events, have been shown to be important in minimizing the effects of livestock grazing on water infiltration rates (Warren et al 1986b).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation has an important influence on infiltration, especially in arid and semi-arid areas (Blackburn et al 1990, Reynolds andReddy 2012), and it can help to maintain higher infiltration rates by increasing soil organic matter, reducing soil bulk density, and reducing compaction and crusting of soil (Mukhtar et al 1985, Radke andBerry 1993). These effects were shown by Bharati et al (2002) who reported that cumulative infiltration in a multi-species riparian buffer in the U.S.A. had the order of: silver maple > grass filter > switch grass > crop fields > pasture.…”
Section: Relationship Between Vegetation Type and Infiltrationmentioning
confidence: 99%